Penggunaan Metode Nonparametrik Untuk Membandingkan Fungsi Survival Pada Uji Gehan, Cox Mantel, Logrank, Dan Cox F - Fitriani Fitriani; Sri Wahyuningsih; Yuki Novia Nasution (Program Studi Statistika FMIPA Universitas Mulawarman, 2016)
Survival analysis is a statistical method that aims to study and model the relationship between risk factors and the study time students to reach graduation. In this study conducted a survival analysis using a nonparametric method. They are Gehan Test, Cox Mantel Test, Logrank Test, and Cox F Test on data of students of Mulawarman University Faculty of Mathematical and Natural Science majoring in Statistics and majoring in Computer Science 2010. The purpose of this research was to compare the of period of study survival function students majoring in Statistics and majoring in Computer Science . This study was conducted using data of 167 students majoring in Statistics and majoring in Computer Science. The results showed that students of majoring in Computer Science longer in studying compared with students majoring in Statistics. For students majoring in Statistics who participated in the selection to go to college through the SBMPTN and SMMPTN study longer than SNMPT. While those who while majoring in Computer Sciences who participated in the selection to go to college through three pathways had the same study time.